Purinergic Receptor Transactivation by theβ2-Adrenergic Receptor Increases Intracellular Ca2+in Nonexcitable Cells - Wayne Stallaert; Emma T. van der Westhuizen; Anne-Marie Schönegge; Bianca Plouffe; Mireille Hogue; Viktoria Lukashova; Asuka Inoue; Satoru Ishida; Junken Aoki; Christian Le Gouill; Michel Bouvier (2017)
The β2 adrenergic receptor (β2AR) increases intracellular Ca2+ in a variety of cell types. By combining pharmacological and genetic manipulations, we reveal a novel mechanism through which the β2AR promotes Ca2+ mobilization (pEC50 = 7.32 ± 0.10) in nonexcitable human embryonic kidney (HEK)293S cells. Downregulation of Gs with sustained cholera toxin pretreatment and the use of Gs-null HEK293 (∆Gs-HEK293) cells generated using the clustered regularly interspaced short palindromic repeat-associated protein-9 nuclease (CRISPR/Cas9) system, combined with pharmacological modulation of cAMP formation, revealed a Gs-dependent but cAMP-independent increase in intracellular Ca2+ following β2AR stimulation. The increase in cytoplasmic Ca2+ was inhibited by P2Y purinergic receptor antagonists as well as a dominant-negative mutant form of Gq, a Gq-selective inhibitor, and an inositol 1,4,5-trisphosphate (IP3) receptor antagonist, suggesting a role for this Gq-coupled receptor family downstream of the β2AR activation. Consistent with this mechanism, β2AR stimulation promoted the extracellular release of ATP, and pretreatment with apyrase inhibited the β2AR-promoted Ca2+ mobilization. Together, these data support a model whereby the β2AR stimulates a Gs-dependent release of ATP, which transactivates Gq-coupled P2Y receptors through an inside-out mechanism, leading to a Gq- and IP3-dependent Ca2+ mobilization from intracellular stores. Given that β2AR and P2Y receptors are coexpressed in various tissues, this novel signaling paradigm could be physiologically important and have therapeutic implications. In addition, this study reports the generation and validation of HEK293 cells deleted of Gs using the CRISPR/Cas9 genome editing technology that will undoubtedly be powerful tools to study Gs-dependent signaling.